Congenital malformations mediated by the adverse effects of teratogenic chemical substance (Research, Society and Development, 2022)
Teratogens are responsible for causing functional, structural, metabolic and behavioral disturbances, which result in malformations in organisms that compromise the period of cellular development and differentiation. Objective: to carry out a systematic scientific survey on the main chemical teratogenic agents and toxic agents with teratogenic potential described in the scientific literature associated with congenital malformations. Methods: through searches and analysis of articles from the last 20 years (2000-2021) without distinction of language available in the search bases: Scielo, Google academic, Pubmed and Virtual Health Library, totaling 36 articles, with only observational studies being chosen. Results: Alarming data were observed in relation to the studies, ending the harmful impact that teratogenic agents have to cause anomalies as well as maternal neglect and, partially, of health professionals from this perspective. Conclusion: Pregnant women are widely exposed to numerous chemical substances, voluntarily or not, which have the potential to deteriorate their health and, above all, that of the fetus. However, teratogenic anomalies are, for the most part, preventable. Thus, the importance of access to information that must be written by health professionals in order to raise awareness, educate or re-educate the population is notorious. Furthermore, it is concluded that, based on the premise that the mother-child relationship is vulnerable and influenced by the environment in which it is placed, therefore, it will be the result of the environment in which it lives.